Assessing the tourism-led growth hypothesis and the demand for tourism in Malaysia / Tang Chor Foon - Tang, Chor Foon (2014)

(untitled)
Tourism is one of the rapidly growing service sectors in the world. This impressive performance has sparked the interest of Malaysia’s government to promote the tourism sector as one of the National Key Economic Areas (NKEA) to transform Malaysia into a high-income nation by 2020. Nevertheless, as economic globalisation gathers momentum, there are criticisms that tourism may not significantly stimulate long-term economic growth as many informal agents bring in illegal workers to Malaysia using the tourism channel as a conduit, and it is hard to differentiate between genuine tourists and those who arrive in search of jobs. This is attributable to the fact that high rates of arrivals may not necessarily equate higher rates of tourism earnings because not all arrivals are genuine tourists. As a latecomer into the tourism industry, of course, Malaysia has also faced a great deal of challenges to obtain genuine tourists and a share of this market. This has revealed the need to assess the role of tourism in Malaysia’s economic growth and also the key factors that inspire tourists’ decision to visit Malaysia. In light of the above concerns, this thesis purports to provide a critical assessment on the tourism-led growth (TLG) hypothesis and the demand for inbound tourism in Malaysia using non-stationary time series and panel data approaches. Essentially, unit root, cointegration and the Granger causality tests are the main econometric techniques used to investigate the issues raised. Generally, the analyses can be segregated into three major parts. First, this thesis examines the validity of the TLG hypothesis in Malaysia at the aggregate level. Second, this thesis attempts to expand the analysis by investigating the validity as well as the iii stability of the TLG hypothesis with respect to tourist arrivals from 12 major touristsgenerating markets. The major tourist-generating markets are Australia, Brunei, China, Germany, Indonesia, Japan, Singapore, South Korea, Taiwan, Thailand, the United Kingdom and the United States. After verifying the validity of the TLG hypothesis in Malaysia, the third component of this thesis is focused on assessing the behaviour of inbound tourism demand in Malaysia. Several main findings are worth noting. First, at the aggregate level of analysis, the results show that the TLG hypothesis is valid. Second, at the disaggregated level of analysis, the results reveal that only 10 out of 12 tourism markets exhibit consistent support to the TLG hypothesis in Malaysia, and most of them were developed countries. This evidence suggests that the TLG hypothesis is still valid in Malaysia, and to optimise resource utilisation, tourism marketing policies should target those markets that could persistently contribute to economic growth. Finally, research on the demand for inbound tourism in Malaysia identified that apart from economic factors, tourists’ decision-making of where and when to go is also highly dependent on environmental quality, security and health factors. Therefore, Malaysia’s government and the industry stakeholders should take into consideration these factors in their planning to attract global tourists to visit Malaysia. In doing so, more genuine tourists can be attracted, and economic growth can be sustained.